Study of carrier concentration in single InP nanowires by luminescence and Hall measurements. (6th January 2015) - Lindgren, David; Hultin, Olof; Heurlin, Magnus; Storm, Kristian; Borgström, Magnus T; Samuelson, Lars; Gustafsson, Anders
Abstract: The free electron carrier concentrations in single InP core–shell nanowires are determined by micro-photoluminescence, cathodoluminescence (CL) and Hall effect measurements. The results from luminescence measurements were obtained by solving the Fermi–Dirac integral, as well as by analyzing the peak full width at half maximum (FWHM). Furthermore, the platform used for Hall effect measurements, combined with spot mode CL spectroscopy, is used to determine the carrier concentrations at specific positions along single nanowires. The results obtained via luminescence measurements provide an accurate and rapid feedback technique for the epitaxial development of doping incorporation in nanowires. The technique has been employed on several series of samples in which growth parameters, such as V/III-ratio, temperature and dopant flows, were investigated in an optimization procedure. The correlation between the Hall effect and luminescence measurements for extracting the carrier concentration of different samples were in excellent agreement.